Effect of stress, depression, and anxiety over periodontal health indicators among health professional students - Gautami S Penmetsa; Pasagadugula Seethalakshmi (Wolters Kluwer Medknow Publications, 2019)
Background: Stress has become a part of one's life, which results in the development of depression and anxiety. This is commonly thought to have a net-negative effect on the efficacy of the immune response, subsequently resulting in periodontal breakdown. Aim: The aim of this study was to assess the effect of depression, anxiety, and stress [DAS] over periodontal health indicators among the health-care professional students. Materials and Methods: The study was conducted in 375 undergraduate health professional students, of which 125 were medical students, 125 were dental students, and 125 were pharmacy students, who were taken from three colleges in Andhra Pradesh. Questionnaires (self-reported oral hygiene questionnaire and DAS Scale questionnaire) were given to the participants, and clinical examination was conducted in all the participants to assess the plaque index (PI), gingival index (GI), probing depth, and clinical attachment level. Statistical analysis was performed using the ANOVA test and post hoc test to compare the psychological parameters with periodontal parameters among three groups of health professional students. P < 0.05 was considered statistically significant. Results: Medical students depicted higher mean stress levels (8.00 ± 2.75) (P < 0.001) and mean DAS score (20.23 ± 6.21) (P < 0.001) than dental and pharmacy students; the mean PI (1.05 ± 0.38) (P < 0.001) and the mean GI (0.72 ± 0.38) (P < 0.001) scores are also increased with stress levels among medical students. Conclusion: Psychological factors have an adverse effect over the plaque levels and gingival status among the students.